EFFECTIVENESS OF SWISS BALL VS FLOOR EXERCISES ON CORE MUSCLE STRENGTH IN ELITE CRICKETERS - K. Sai sudha (International Journal of Physiotherapy, 2015)
Background: Cricket is one of the most popular game in India played by men and women of all ages. The increased physical demands on the players may be associated with an increased risk of injuries. Core muscle strength is important to prevent risk of injuries in elite cricketers. The beginners in the cricket must have enough strength of core muscles, as core is the bridge between upper and lower limbs. So, it should be strong enough to prevent low back and lower limb injuries in cricketers. The aim is to determine the effectiveness of swiss ball exercises versus floor exercises on core muscle strength in elite cricketers. The objective is to study and compare the effectiveness of swiss ball exercises and floor exercises in elite cricketers in terms of back strength. Method: The total number of students in this study were 30 eilte cricketers between 16-25 years out of which 15 subjects were included each in floor exercise(n=15) and swiss ball group(n=15). Back strength was measured before and after the intervention of 6 weeks using isokinetic analyser. Results: After the analysis, the results revealed significant improvement of back strength in both the groups(p< 0.00). The swiss ball group showed significant results when compared with floor exercise group. Conclusion: Although the study showed beneficial results in both the groups, the results reflected that swiss ball group had better improvement of core muscle strength than the floor exercise group.